Hemoglobinopathy correction with CRISPR or not; gene therapy is the solution - Bader Al Alwan; Arwa A Alsubait; Bahauddeen M Alrfaei (Wolters Kluwer Medknow Publications, 2020)
Hemoglobin (Hb) disorders or hemoglobinopathies are groups of blood conditions involving inherited genetic diseases - mostly as single-gene autosomal recessive - that lead to the formation of abnormal Hb structure or inadequate to no production of globin chains in Hbs. Disorders of Hb are a global concern since these diseases can cause severe morbidity and early mortality of the affected populations. Treatments vary between chemicals and molecular approaches. The most promising approach is Hb correction. However, the stability of the correction faces a big challenge along with safety concerns. It is worth noting that most of the inherited hemoglobinopathies share common clinical presentations and laboratory findings, although some have distinct features. Hemoglobinopathies with emphasis on recent advances in gene therapy targeting sickle cell disease and thalassemia are discussed in this review.